Literatura, Cinema, Adaptação: flor do deserto no espaço das narrativas femininas contemporâneas - Meira, Danielle Alexa Barbosa (2017)
The present research focuses on the analysis of Waris Dirie and Cathleen Miller's autobiography, Desert flower (2001), and the homonymous film adaptation, by Sherry Hormann (2009), within the current scene of female autobiographical narratives, observing how the memorialist element acts in the process of resignifying the literary and the fictionalizing of history, also focusing on the reconfiguration of Waris Dirie's black female identity, in literature and cinema, and how it reverberates in contemporary social scenes. Of bibliographical character, the investigation discussed the construction of these narratives, both literary and filmic, considering their respective contexts of production and consumption. In this sense, the adaptation process constituted an important point of analysis in the work, because it enables the narratives specific ways of re(creating) and re(telling) the stories. The somali nomadic’s life trajectory, who ran away at 13 years old from the desert and arrived in London, where she became a top model, transcends the discourse of “surpassing” and points to a narrative that raises the questioning of what it means “to be a woman” inside and out of her culture. As a matter of fact, the character, as a child, went through the female genital mutilation ritual, that affects femaleness both physically and psychologically. The transit space between the cultures allowed the character to become aware of this body and female subject notably marked by issues of gender, race and class. Therefore, narratives by women in contemporary times, while opening an emergence space of silenced and oppressed women voices in diverse cultural contexts, reconfigures their identities; they move, then, between the aesthetic and the political. The analysis is supported by theoretical contributions of authors such as Lejeune (2008), Arfuch (2011), Candau (2012) and Halbwachs (1990), in the autobiographical, memorialistic and identity approach; Hutcheon (2011), Bazin (2014) and Mascarello (2009), regarding the cinematographic adaptation and Hollywoodian production context; Hall (2003, 2011) and Almeida (2015), in the diaspora question and Davis (2016), Saffioti (2015) and Del Priori (2009), in the gender, race and class discussions. Thus, the chosen theories were crucial in understanding the corpus analysis, pointing out the significant problematics and (re)creating the literary and filmic meanings in the current social context.